The genomic landscape of metastatic clear cell renal cell carcinoma after systemic therapy. Issue 12 (5th April 2022) - van der Mijn, Johannes C.; Eng, Kenneth W.; Chandra, Pooja; Fernandez, Evan; Ramazanoglu, Sinan; Sigaras, Alexandros; Oromendia, Clara; Gudas, Lorraine J.; Tagawa, Scott T.; Nanus, David M.; Faltas, Bishoy F.; Beltran, Himisha; et al.
Abstract : Primary clear cell renal cell carcinoma (ccRCC) has been previously characterized, but the genomic landscape of metastatic ccRCC is largely unexplored. Here, we performed whole exome sequencing (WES) in 68 samples from 44 patients with ccRCC, including 52 samples from a metastatic site. SETD2, PBRM1, APC and VHL were the most frequently mutated genes in the metastatic ccRCC cohort. RBM10 and FBXW7 were also among the 10 most frequently mutated genes in metastatic tissues. Recurrent somatic copy number variations (CNV) were observed at the previously identified regions 3p25, 9p21 and 14q25, but also at 6p21 ( CDKN1A ) and 13q14 ( RB1) . No statistically significant differences were found between samples from therapy‐naïve and pretreated patients. Clonal evolution analyses with multiple samples from 13 patients suggested that early appearance of CNVs at 3p25, 9p21 and 14q25 may be associated with rapid clinical progression. Overall, the genomic landscapes of primary and metastatic ccRCC seem to share frequent CNVs at 3p25, 9p21 and 14q25. Future work will clarify the implication of RBM10 and FBXW7 mutations and 6p21 and 13q14 CNVs in metastatic ccRCC. Abstract : Molecular analysis of lesions that drive progression of kidney cancer has been performed with primary kidney tumours. In this manuscript, we analysed genomic alterations present in various metastatic lesions. We discovered two genes and chromosomal locations that are frequently altered, particularly in metastatic lesions, as well as a pattern of alterations that might be associated with poor prognosis.